The benthic insect fauna of the blackwater forest stream Rio (Manaus, Amazonas): patterns of population dynamics and their implications for ecosystem stability - Walker, I. (Amazoniana, 2003)
The annual pattern of emergence of aquatic insects with benthic larvae stages of a small, Central Amazonian blackwater river is presented. This pattern is primarily a function of the annual inundation cycle ("flood pulse"; JUNK et al. 1989), but non-random variations within sampling-sites and -periods suggest that the organisms are choosing favourable micro-habitats.
Keywords: Insetos Aquáticos